Scientific production about social appropriation of scientific knowledge within the scope of Social and Human Sciences: A literature review in the period 2002-2022 - Macucule, Augusto Júnior [UNESP]; Valentim, Marta Lígia Pomim [UNESP] (Pro-Metrics, 2023)
Objective. Scientific production on the social appropriation of knowledge presents diverse concepts and understandings, and there is no consensus in the existing scientific literature about the theme. The aim is to understand the conceptual variations on the ‘appropriation of scientific knowledge’ within the scope of Social and Human Sciences based on a bibliographic review in national and international databases. Design/Methodology/Approach. The research is of a qualitative and quantitative nature, of the bibliographic type, and for this purpose, a systematic literature review was used, covering the period between 2002 and 2022. Results/Discussion. The social appropriation of knowledge in conceptual terms presents a variation related to the geographic, epistemic context, and political. Terms such as scientific culture, social production of knowledge, social diffusion of knowledge, and public perception of science, among others, are associated with social appropriation of knowledge. The conceptual variation on social appropriation of knowledge needs to be understood considering the production, dissemination, and uses of knowledge by different users of information and knowledge. Conclusions. Knowledge production occurs in universities, research centers, and public and private organizations committed to disseminating and appropriating scientific knowledge. It is worth highlighting that the cyclical process through which the social appropriation of knowledge occurs depends on the scientific and technological policies of the countries.
Produção científica sobre apropriação social do conhecimento científico no âmbito das Ciências Sociais e Humanas: uma revisão da literatura no período de 2002-2022
Keywords: conceptual variation; scientific divulgation; Social and Human Sciences; social appropriation of knowledge; units of production and knowledge appropriation